การสร้างข่าวของรายการข่าวท้องถิ่นของสถานีโทรทัศน์เคเบิ้ลทีวีจากสองสถานีในจังหวัดกำแพงเพชร - ณัฐพงศ์ จันทรางกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The study of the news making of local news programs of two cable television stations in Kamphaengphet province has objectives to know the caracteristics of news making of local news programs in Kamphaengphet province as well as responding extravagant expectations of news audiences towards local news programs broadcasting via two cable television stations in Kamphaengphet province. The research shows that making news by both cable television stations has the news caracteristics which can be divided into two manners. That is to say, firstly making news from real event, but expanding or adding points. Secondly, making news from pseudo-events by creating, preparing and stimulating as it happens naturally. For the responding of the extravagant expectation from local news audiences can be categorized into two aspects. (1) news producer stimulates the extravagant expectation by presenting person image in local news which is considered as People source and local people image (2) news source activates the responding of the extravagant expectation because it encourges images on news program in order to do Public Relations for persons, organization or show the role and the responsibility of news source.